“Still-Vexed”: Laura E. Richards’s Captain January and Shakespeare - Josephine Sharoni (European Journal of American Studies)
This paper examines the connection between Laura E. Richards’s Captain January and Shakespeare’s The Tempest, considering how the allusions to the play might change our reading of the story. The discussion is then widened to show the importance of Shakespeare for Richards and her manner of relating to his work, implying that Captain January is still relevant to the teaching of Shakespeare.